Pemberdayaan petani aren (Arenga pinnata Merr) rakyat melalui diversifikasi produk nira aren di Desa Mabar Kecamatan Bangun Purba Kabupaten Deli Serdang - Sri Wahyuni (Unri Conference Series: Community Engagement, 2019)
Palm sap has the potential to be used as sugar because it contains the dominant sugar component, the type of sucrose. Palm Sugar from Mabar Village, Bangun Purba District is known as truly pure palm sugar. The problem faced by palm farmers in this village is that the palm sugar business has not yet become a reliable business to improve the family economy. The purpose of this community service activity is to facilitate the sugar palm farmers so they can improve their businesses and become productive businesses. The method used in this activity is counseling / education, technology implementation from the Community Service Team. The results achieved in this activity partners namely sugar palm farmers are given a way of socializing processing, implementation of tools from traditional to modern. The results achieved are palm sugar syrup and palm sugar.